Heterosis for seed yield and its components in sesame under supplementary irrigation - Hassan, Mohamed; Ibrahim, Abu Elhassan; Ali, Eltahir; Gamos, Gamal (Gezira Journal of Agricultural Science, 2013)
Experiments were carried out during autumn in 2009 at two irrigated locations (Abu Naama and Sinnar) on clay plains of central Sudan. Fourteen sesame genotypes were crossed in line x tester mating scheme and heterosis over mid parent was estimated for the seed yield and its components in 49 F 1 top cross hybrids. The crosses and their parents were arranged in a randomized complete block design with three replicates. The traits measured were days to 50% flowering, days to maturity, plant height, number of branches per plant, number of capsules per plant, capsule length, 1000-seed weight and seed yield. Among the crosses evaluated across the two locations: T3 x L3 and T1 x L5 combined high heterosis for early maturity with high seed yield. This indicates that the crosses were earlier and high yielders than their parents and could be utilized to develop genotype (s) suitable for locations in central Sudan, that is, characterized by varying and low total rainfall. The top four ranking crosses for seed yield across locations were T6 x L3 (1108 kg/ha), T6 x L7 (1023 kg/ha), T1 x L5 (1022 kg/ha) and T5 x L5 (1014 kg/ha). The highest percentage of mid parent heterosis for seed yield across sites were given by T3 x L3 (52%) followed by T3 x L7 (44%), T5 x L7 (44%) and T1 x L5 (43%). These crosses can be used to develop high yielding sesame hybrids through hand emasculation and pollination for further testing in multilocations trials.    أجريت هذه التجارب في السودان أثناء الفصل الممطر عام 2009 في أبو نعامة و سنار باستخدام تصميم القطاعات العشوائية الكاملة بثلاث مكررات بإتباع تحليل سلالة x مختبرline x tester analysis)) والذي شمل أربعة عشر أباً، وسبعة آباء ذكورmale parents) ) وسبعة آباء إناث  (female parents) معطية 49 هجيناً. زرعت التجارب في يوم 7 يوليو 2009 في كلا الموقعين. الصفات التي تمت دراستها شملت عدد الأيام حتى 50% إزهار، عدد الأيام حتى النضج، طول النبات، عدد الفروع في النبات، عدد الكبسولات في النبات، طول الكبسولة، وزن 1000 بذرة و إنتاجية البذور. وجد أن الهجن مبكرة في الأزهار وفترة النضج مقارنة بالآباء. الهجنT3 x L3  و T1 x L5أظهرت قوة هجين عالية في إنتاج البذور والتبكير في الإزهار والنضج. هذه الهجن يمكن استخدامها في المناطق قليلة الأمطار. أعلى الهجن إنتاجية عبر الموقعين هي  T6 x L3(كجم/هكتار  (1108، T6 x L7 (كجم/هكتار (1023، T1 x L5(كجم/هكتار 022 (1،T5 x L5(كجم/هكتار1014 (و T6 x L6 (كجم/هكتار 965(). الهجن التي أظهرت أعلى قوة هجين عبر الموقعين هي(52%) T3 x L3, T3 x L7 (44%),T5 x L7 (%44) و T1 x L5 (%43). ومن خلال هذه الدراسة نوصي باستخدام هذه الهجن بعد إجراء بعض الاختبارات الخاصة بالإنتاجية في مواقع ومواسم مختلفة.